Development of Antioxidant COX-2 Inhibitors as Radioprotective Agents for Radiation Therapy-A Hypothesis-Driven Review - Markus Laube; Torsten Kniess; Jens Pietzsch (MDPI AG, 2016)
Radiation therapy (RT) evolved to be a primary treatment modality for cancer patients. Unfortunately, the cure or relief of symptoms is still accompanied by radiation-induced side effects with severe acute and late pathophysiological consequences. Inhibitors of cyclooxygenase-2 (COX-2) are potentially useful in this regard because radioprotection of normal tissue and/or radiosensitizing effects on tumor tissue have been described for several compounds of this structurally diverse class. This review aims to substantiate the hypothesis that antioxidant COX-2 inhibitors are promising radioprotectants because of intercepting radiation-induced oxidative stress and inflammation in normal tissue, especially the vascular system. For this, literature reporting on COX inhibitors exerting radioprotective and/or radiosensitizing action as well as on antioxidant COX inhibitors will be reviewed comprehensively with the aim to find cross-points of both and, by that, stimulate further research in the field of radioprotective agents.